EFFECT OF THE SCREENS RADIANT REFLECTANCE ON THERMAL TRANSPORT PROCESS IN THE CLADDING STRUCTURES - V. D. Sizov; L. V. Nesterov; V. M. Kopko (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2016)
The article analyses variants of the heat insulating layers disposition in relation to the cladding load-carrying structures and demonstrates prime advantages and drawbacks of the three variants. The authors notice that from the heat-engineering viewpoint the variant with exterior side winterization is the most favourable. However, utilizing micromodules as heat-insulating layers screened with leafing aluminum makes it necessary to account for the screens reflecting power. It allows reducing the irradiating component in the combined value of thermal transport through the enclosure and consequently raises the structure thermal resistance or, with parity of these values, leads to lower thickness of the heat-insulating layer. The known data applied for calculating the total heat transmission helps demonstrate reduction of the general heat flux value by 1.4 times, and the heat transmission resistance by 1.76 m2 deg./W. This allows reducing thickness of the heat-insulating layer (with regard of two screens) by 0.07 m. Computations illustrate the fact that account for the radiant reflectance of screening enables lowering the rated heat flux passing through the enclosure. Which again allows decreasing the structure thermal resistance and its general thickness (by 70 mm) at the expense of small thickness of the heat insulation of micromodules. The humidity regime calculations establish good acceptability of the enclosure service conditions in winter. The period will see no real water vapour condensation. The plotted diagrams of the cladding heat-and-humidity conditions demonstrate that condensation zones do not affect the layer of thermal insulation (micromodules). And the condensation zone with reduction of the heat-insulating layer appears only during ‘severe’ outside temperature conditions of a cold month. Reduced to 230 mm thickness of the wall construction allows utilizing ‘old’ stock of forms with prefabricated panels in parallel with energy saving during thermal treatment.